DEVELOPMENTAL CHARACTERISTICS INFLUENCED BY FLOW IN PSYCHOLOGY - Ahmad Noviansah (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
Development is a pattern of change that begins at the time of conception (conception) and berkanjut throughout the life span in the development of children, it must be instilled character teaching in the character teaching is very important, because the ideal society is when the community has a good character and character. Quality characters need to be touched and nurtured from an early age. Childhood ages 0 to 6 years is a golden priode of growth, this is the most appropriate time to leverage and develop all potentials in the child. The development of this potential is not only from the intellectual sis, but also develops other aspects such as character.